PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN KESIAPAN DAN PRESTASI BELAJAR SISWA (Studi Tindakan Kelas Pada Mata Pelajaran Bahasa Indonesia Kelas V SD Negeri 4 Merapi Selatan Kabupaten Lahat ) - Sukardi Sukardi (UNIB Press, 2020)
Thisresearch aimstodescribethe applicationofcooperativetype of learning modeltalking stickto increasethereadinessandthe students’achievementat IndonesiansubjectofthefifthclassatSD Negeri4MerapiSelatan.Thedesignof researchusedisclassroomactionresearchandthequetiontexperiment.Thesubjects oftheresearcharethestudentsofV.aatthesecondsemesteroftheacademicyear 2019/2020atSDNegeri1MerapiSelatan.Forthesamplesof quetiontexperimentare V.b and V.c nstrumen penelitian ini menggunakanlembar observasi dan tes. The instrumentsusedisthe observationsheet andtest.The datais analizedwithusingthe statisticdescriptive,mean,thepercentageandT-test.The resultshowsthatthe application of cooperative type of learning model talking stick can increase the readinessandthestudents’achievementofthestudentsofthefifthclassatSDNegeri 4Merapi SelatanLahatregency